THE WESTERN BALKANS PERSPECTIVES IN THE CONTEXT OF SINO-EUROPEAN RELATIONS - Ilik, Goran; Shapkoski, Vesna (Horizons - International Scientific Journal, 2021)
The Western Balkans perspectives as an integral part of the EU is a many time declared commitment throughout the past decades. By emphasizing it as a joint vision, the EU tends to strengthen and maintain not only peace and stability among the six Western Balkans countries (WB6) but also economic and political prosperity transposing its norms and values. Nonetheless, this process is taking too long, leaving space for foreign influences at different times. The economic expansion of China came meanwhile, consisted mainly of infrastructure investment and development, as part of the Belt and Road Initiative and 17+1 framework. As it is growing exponentially, it is clear that thesedirect investments are highly related to China’s geopolitical interests in the region.The biggest issue here is that China’s values (and its civilizational matrix – predominantly Confucian) are different from the EU’s to such an extent that the parallel presence of both in the Western Balkans could lead to numerous controversial choices of the governments, which threaten to slow down, to sabotage and to complicate the long and arduous process of eurointegration. In the end, it can be concluded that the Western Balkans is too small for the presence of more great actors, and thus, the perspectives of the Western Balkans belong to European civilization.